2020
DOI: 10.3389/fmed.2020.00503
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy for Increased International Efforts for Antimicrobial Stewardship Actions in Low-and Middle-Income Countries on Behalf of Alliance for the Prudent Use of Antimicrobials (APUA), Under the Auspices of the International Society of Antimicrobial Chemotherapy (ISAC)

Abstract: Antimicrobial stewardship (AMS) is a set of coordinated strategies to improve the use of antimicrobials, to enhance patient outcomes, reduce antimicrobial resistance, and decrease unnecessary costs. The pioneer years of AMS were restricted to high-income countries (HIC), where overconsumption of antibiotics was associated with emergence of multidrug-resistant (MDR) bacteria. AMS in low-and middle-income countries (LMIC) is also necessary. However, programs effective in HIC may not perform as well in LMIC, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Hospitals in LMIC were more often confronted with unavailability of prescribing guidelines, insufficient laboratory capacity and suboptimal use of the available laboratory services. Indeed, in addition to strengthening the microbiological laboratory capacity in LMIC, efforts should be directed at promoting diagnostic stewardship and improving the communication interface between clinicians and laboratory services [ 48 , 49 ]. Many hospitals also reported a lack of knowledge on good prescribing practices and a lack of cooperation from prescribers as key barriers to a successful AMS programme.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals in LMIC were more often confronted with unavailability of prescribing guidelines, insufficient laboratory capacity and suboptimal use of the available laboratory services. Indeed, in addition to strengthening the microbiological laboratory capacity in LMIC, efforts should be directed at promoting diagnostic stewardship and improving the communication interface between clinicians and laboratory services [ 48 , 49 ]. Many hospitals also reported a lack of knowledge on good prescribing practices and a lack of cooperation from prescribers as key barriers to a successful AMS programme.…”
Section: Discussionmentioning
confidence: 99%
“…AMS programmes in LMICs generally encounter challenges of limited financial and physical resources available for implementation including substandard lab practices, lack of well-trained staff, insufficient opportunities for continuing professional development and difficulties in deploying prescription-based stewardship strategies. 26 27 Despite numerous challenges and limited, poor-quality evidence available, 30 effective AMS programmes can be feasible in these settings although contextualisation is essential in this implementation. 7 The need for contextualisation in LMICs was also highlighted in several qualitative and mixed-methods AMS studies.…”
Section: Discussionmentioning
confidence: 99%
“…The current status of microbiology in LMICs would not allow for a desirable level of support to AMS programmes. 26 However, improvements can be made even within resource-constrained conditions. Our study showed that simply compiling the current data and presenting the summary data in the AMS meetings has stimulated the discussions on the immediate and long-term actions to improve the problem.…”
Section: Discussionmentioning
confidence: 99%
“…National and international advocacy as well as advocacy through civil societies is particularly important in resource-limited areas [ 60 ]. Through the effort of governmental and international collaborations to share established strategies, policies and skills; resource-limited countries may benefit from the experience of countries with existing AMS programmes.…”
Section: Recommendations For Adaptations Of Clinical Practice In Tmentioning
confidence: 99%
“…Through the effort of governmental and international collaborations to share established strategies, policies and skills; resource-limited countries may benefit from the experience of countries with existing AMS programmes. This can provide a framework to kickstart and expand AMS programmes without unnecessary delays [ 60 ].…”
Section: Recommendations For Adaptations Of Clinical Practice In Tmentioning
confidence: 99%